Optimalisasi Partisipasi Mahasiswa Penerima KIP-Kuliah dalam Program MBKM untuk Mendukung Pencapaian SDGs di Indonesia - Ismail, Ismail; Beta, Nurlatifa; Akbar, Imam; Rahmat, Rahmat; Alfrida, Muthmainnah; Sunarti, Sunarti (Universitas Muhammadiyah Enrekang, 2025)
Inclusive and quality education is a key element in supporting the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4. This study aims to evaluate the effectiveness of the KIP-Kuliah program in enhancing student participation in the Merdeka Belajar-Kampus Merdeka (MBKM) program at Universitas Muhammadiyah Enrekang, focusing on the barriers and support factors influencing their engagement. The research employed a quantitative descriptive approach, with data analyzed using descriptive statistics and Pearson correlation. Data were collected through MBKM participation questionnaires and semi-structured interviews with KIP-Kuliah recipients and non-recipients. The total participants comprised 209 seventh-semester students, including 107 KIP-Kuliah recipients and 102 non-recipients. The results indicate that 92.52% of KIP-Kuliah recipients participated in MBKM programs, compared to 80.39% of non-recipients. Major barriers included financial constraints, insufficient institutional support, and limited access to information. Information was found to have the most significant correlation with student participation (r = 0.949, p < 0.01). The findings have implications for reducing socio-economic disparities in higher education, improving students’ employability, and strengthening a more inclusive education system. Strategic recommendations include enhanced financial support, improved information dissemination, and mentoring training to increase student engagement in MBKM programs. This study extends our understanding of the synergy between financial support and practice-based learning, providing a foundation for further research on the long-term impact of MBKM on students’ career success.